2020
DOI: 10.1111/dth.14254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical selection criteria in new clinical trials of hidradenitis suppurativa: External validity and implications on the daily clinical practice

Abstract: Introduction: There are an increasing number of biologic drugs in the pipeline for treating hidradenitis suppurativa (HS). Clinical trials for these drugs usually share the same clinical selection criteria. Objectives: (a) To describe the clinical profile of HS patients receiving first-line biologic treatment in an HS clinic setting, (b) to assess how this population would meet clinical criteria to participate in a clinical trial, and (c) to assess treatment effectiveness at week 16 in eligible vs non-eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Regarding disease severity, Barrea et al found that adherence to the MD negatively correlated to HS severity, evaluated by Sartoriusscore [17]. In agreement with them, we observed that the adherence to the MD is negatively associated with the IHS4 score and self-reported disease activity [29,36]. Adherence to the MD has been also associated with disease severity in psoriasis [20,34].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding disease severity, Barrea et al found that adherence to the MD negatively correlated to HS severity, evaluated by Sartoriusscore [17]. In agreement with them, we observed that the adherence to the MD is negatively associated with the IHS4 score and self-reported disease activity [29,36]. Adherence to the MD has been also associated with disease severity in psoriasis [20,34].…”
Section: Discussionsupporting
confidence: 89%
“…There are clinical trials that observed similar effectiveness and tolerability between originator adalimumab and biosimilar adalimumab in psoriasis [20]. However, the external validity of clinical trials might be low, as they usually have straight eligibility criteria, and the tool used to assess effectiveness may not be reliable in HS [21]. For example, clinical trials are frequently conducted in naïve patients to biologic treatment, and pregnant women, elderly, and very severe patients are not allowed to be included [20].…”
Section: Discussionmentioning
confidence: 99%
“…Factors independently associated with an increase in OCP effectiveness were a shorter HS duration, worsening in relation to the menstrual cycle and being receiving a concomitant therapy. A long disease duration is related to the presence of scars and draining tunnels [ 36 ], when OCPs are less effective. It was shown that the worsening of HS with the menstrual cycle was almost independently related to the percentage of AN reduction in patients with OCP treatment.…”
Section: Discussionmentioning
confidence: 99%